Make It Till You Break It: Toward a Typology of De‐Commemoration. Issue 2 (29th March 2022) - Adams, Tracy; Guttel‐Klein, Yinon
Abstract : Challenging traditional understandings of the past, the toppling of statues of prominent historical figures highlights the ongoing negotiation of collectives with their pasts and the importance of commemoration practices in meaning‐making processes. In Israel, this phenomenon is complex and nuanced, despite its appearance as a lack of concern with revisiting the past. Accordingly, this research examines current practices of de‐commemoration in Israel as a unique tool of social and political protest. Drawing upon qualitative and multimethod studies that combine text analysis, in‐depth interviews, participant observations, and archival work, we suggest a hierarchical typology of de‐commemoration—desecration, reframing, and planned obsolescence—establishing how each practice renegotiates with the present through alteration of the form of commemorated material. Questioning previous understanding regarding the prominence of the past, and building on the unique Israeli case, analysis demonstrates how practices of de‐commemoration are influenced by the transnational climate of change, consciously adhering to the need to realign commemorated pasts in line with the conflicts of the present. Commemoration and de‐commemoration thus complement and build on one another, constituting the civil religion of any given collective. Contributing to current discussions regarding the normative attributions of collective memory, we show how nothing is set in stone.